Implementação de um modelo murino de infecção pelo chikungunya vírus para o estudo da patogênese e identificação de potenciais alvos terapêuticos - Thaiane Pinto Moreira (2018)
Chikungunya fever is an infectious viral disease that has as etiological agent the Chikungunya virus (CHIKV), and is mainly transmitted by the mosquitoes Aedes aegypti and A. albopictus. The most important clinical signs of disease include fever, headache, erythematous and maculopapular rash, back pain, myalgia, and symmetrical biphasic arthralgia, which in majority of cases evolve to chronic. Until now, there is no specific antiviral treatment or vaccine available to the treatment of chikungunya fever. The development of models to study the interaction between the virus and its host may be used as a basis for understanding factors associated with the disease, as well as for testing new antiviral and/or anti-disease therapies In this context, the aim of this work was to implement a model of CHIKV infection in immunocompetent mice in order to study the pathogenesis of the disease and to identify possible therapeutic targets. Wild-type (WT) mice of the C57BL/6j lineage were infected with CHIKV and their respective uninfected controls were also used. An infection kinetics (1, 3, 7 and 14 days) was performed after CHIKV inoculation and several parameters were evaluated. Our results shows that CHIKV infection in 4 weeks old mice induced strong leukopenia, predominantly composed of lymphocytes, in comparison to uninfected control mice. In addition, we observed a higher inflammatory response to infection, as demonstrated by an increased recruitment of neutrophils and macrophages to the sites of infection, increased production of several inflammatory mediators, such as the cytokines (TNFα and IL-6) and chemokines (CCL2, CCL3, CCL4, CLL5, CXCL-2 and CXCL-9) and elevated titers of viable viral loads in the rear foot pad, popliteal lymph node, quadriceps and spleen of CHIKV infected mice. Furthermore, these mice showed a sensitive alteration in response to a nociceptive stimulus (hot plate test), inflammatory articular hypernociception, and important histopathological changes in the ankle and knee joints, even without occurrence of bone loss or changes in motor function. Finally, the role type I interferons (IFNα and IFNβ) during CHIKV infection was evaluated. We have demonstrated, through the use of mice deficient to this receptor (IFNα/βR-/-), that the course of the disease 18 induced by CHIKV infection is much more severe and is associated with a high mortality rate and a worsening of all clinical and inflammatory parameters described above. Overall, those results demonstrate the development of an experimental model in young WT mice that mimics a great number of parameters of CHIKV-induced disease in humans. Furthermore, we demonstrate the crucial protective role of type I interferons (IFNα and IFNβ) in the host's response to the infection. Those models will contribute in the future to the elucidation of mechanisms associated with the pathogenesis of the CHIKV- host interactions and to the development of new antiviral and anti-disease therapeutic potentials.